An attempt to determine the cause of the strong tremor responsible for a rockburst in a hard coal mine based on numerical modeling and spectral parameter - Wojtecki, Lukasz; Krawiec, Krzysztof; Ćwiękała, Mateusz; Dzik, Grażyna (Geology, Geophysics and Environment, 2024)
Seismic and rockburst hazards represent significant challenges during the longwall mining of coal seams. One analytical approach to assess the potential for rockburst hazards involves reconstructing the stress conditions within the rock mass. This article reports on the findings from three-dimensional (3D) numerical modeling aimed at examining the distribution of maximum shear stress within the rock mass amid the longwall mining operations of the 703/1 coal seam in a mine situated in the Upper Silesian Coal Basin, Poland which was disrupted by a rockburst incident. On the day of the rockburst, substantial concentrations of maximum shear stress were identified in a thick sandstone layer proximate to the boundary of the overlying 624 coal seam located significantly above the 703/1 coal seam. The calculated maximum shear stress demonstrated an increase of approximately 80% over the values observed in the absence of edge effects. Furthermore, a higher concentration of maximum shear stress was identified within the geologically weaker strata adjacent to the 703/1 coal seam. These observations facilitated the classification of the examined rockburst as a stress-stroke phenomenon. Additionally, the study determined the spectral parameters of the tremor, which possessed an energy of 9.8 × 107 J and triggered the analyzed rockburst. The ratio of the seismic energy of S and P-waves confirmed a shear mechanism in the focus. The scope of inelastic deformation within the focal zone was also quantified. Following the event, the rock mass that had been destressed due to the significant tremor and subsequent rockburst exhibited reduced seismic activity upon the resumption of longwall mining of the 703/1 coal seam.